2019
DOI: 10.1136/bmjopen-2019-034594
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the experiences and perspectives of substitute decision-makers involved in decisions about deceased organ donation: a qualitative study protocol

Abstract: IntroductionIn Canada, deceased organ donation provides over 80% of transplanted organs. At the time of death, families, friends or others assume responsibility as substitute decision-makers (SDMs) to consent to organ donation. Despite their central role in this process, little is known about what barriers, enablers and beliefs influence decision-making among SDMs. This study aims to explore the experiences and perspectives of SDMs involved in making decisions around the withdrawal of life-sustaining therapies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…With research in this context focussing on enabling informed decisions and increasing donation rates (Ashkenazi & Cohen, 2015 ; Marck et al, 2016 ), connections between in-hospital experiences and ongoing adjustment are under-explored, especially in relation to Donation after Circulatory Determination of Death (DCDD, Dimo, 2019 ; Naef et al, 2020 ; Sque et al, 2018 ; Takaoka et al, 2020 ; Zheng et al, 2020 ). Identifying and responding to family and staff needs in this complex environment are challenging tasks for HCPs (Kerstis & Widarsson, 2020 ; Shariff et al, 2017 ; Simonsson et al, 2020 ; Walker & Sque, 2019 ; Zellweger et al, 2017 ), highlighting the need for training to improve end-of-life care and peer support (Chan et al, 2020 ; Crawshaw et al, 2019 ; Witjes et al, 2017 , 2019a , 2019b ).…”
Section: Introductionmentioning
confidence: 99%
“…With research in this context focussing on enabling informed decisions and increasing donation rates (Ashkenazi & Cohen, 2015 ; Marck et al, 2016 ), connections between in-hospital experiences and ongoing adjustment are under-explored, especially in relation to Donation after Circulatory Determination of Death (DCDD, Dimo, 2019 ; Naef et al, 2020 ; Sque et al, 2018 ; Takaoka et al, 2020 ; Zheng et al, 2020 ). Identifying and responding to family and staff needs in this complex environment are challenging tasks for HCPs (Kerstis & Widarsson, 2020 ; Shariff et al, 2017 ; Simonsson et al, 2020 ; Walker & Sque, 2019 ; Zellweger et al, 2017 ), highlighting the need for training to improve end-of-life care and peer support (Chan et al, 2020 ; Crawshaw et al, 2019 ; Witjes et al, 2017 , 2019a , 2019b ).…”
Section: Introductionmentioning
confidence: 99%
“…As experts of their lived healthcare experiences, patients and their caregivers can also provide valuable insight into potential barriers and enablers faced throughout the care pathway and during research. Patients can provide crucial insight on ethical issues, such as providing reassurance that the study is appropriate, and feedback on how to handle difficult discussions, such as approaching and recruiting patients at sensitive times or for sensitive topics [6,7]. Recent reviews indicate patient engagement is gaining traction in clinical research [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…As experts of their lived healthcare experiences, patients and their caregivers can also provide valuable insight into potential barriers and enablers faced throughout the care pathway and during research. Patients can provide crucial insight on ethical issues, such as providing reassurance that the study is appropriate, and feedback on how to handle di cult discussions, such as approaching and recruiting patients at sensitive times or for sensitive topics (6,7). A recent systematic review has also shown that patient engagement is associated with modestly improved clinical trial recruitment (8).…”
Section: Introductionmentioning
confidence: 99%